Analisis Pengaruh Non Financial Measures Disclosure, Corporate Governance Dan Kualitas Audit Terhadap PerformanceMelalui Cost Of Equity Perusahaan - Chandra Situmeang; Esna Muriana Hutabarat (Universitas Negeri Medan (UNIMED), 2017)
Abstract: This study aims to determine the effect of non-financial measures of disclosures, corporate governance and the quality of audits of performances through the company’s cost of equity, at a manufacturing company in Indonesia Stock Exchange 2014 Performance period is the achievement of the company. The cost of equity is the rate of return expected by investors. This study uses three variables, namely nonfinancial measures disclosure, corporate governance, quality audit. The population of this research is all manufacturing companies listed in Indonesia Stock Exchange in 2014. The source of this research is secondary data obtained by downloading the annual financial statements in www.idx.co.id sites, the stock price data at the site www.yahoofinance.com, and the SBI interest rate of sites www.bi.go.id the methods used to analyze the data is statistical path analysis. The result showed that the analysis of the influence of non-financial measures of disclosure, corporate governance, and audit quality is not partial effect on the performance and cost of equity of the company. Meaning broad Disclosure NFM, increase the portion of independent commissioner, and the increase of audit quality has not been able to convicethe investors about the prospect the company. Conviction about the company prospect is the important thing to reduce cost of equity and the decreasing of cost of equity will increase the company performance.